(untitled) - Archer, C. J. ([Melbourne], 2023)
"When a set of bound manuscripts written on magician-made paper is brought to the Glass Library, Sylvia and the professor send the owner away. After all, the library collects books about magic, not containing it. But the murder of the bookbinder who bound them sees the books returned to the library, along with Gabe in his role as a consultant for Scotland Yard. WHen his investigation uncovers a link to Sylvia's past, they're even more determined to find the murderer. But they're not the only ones searching for answers e has gone to great lengths to find the truth behind the binding of the books. The hunt for the killer leads them to dark corners of London and unscrupulous players with much to gain by owning the collection. It also leads to the discovery of long-buried secrets, and staggering revelations that shed light on Sylvia's past."--Provided by publisher.
Keywords: Fiction; Nineteen twenties; Investigation; Fiction; Murder; Bookbinders; Fiction; England; Fiction; Books; Fiction; Libraries; Fiction; Librarians; Fiction; Magicians; Magic; Fiction; London (England); Fiction; Fantasy fiction; Detective and mystery fiction; Novels